PERSEPSI PETANI TERHADAP KELEMBAGAAN PENYULUHAN POLA SISTEM INTEGRASI SAPI-KELAPA SAWIT (SISKA) DI KABUPATEN KAMPAR - Imam Fahrorozi; Susy Edwina; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to identify institutions and to know the perception of oil palm farmer’s for institutional support Integration System of Oil Palm Cattle Programs (SISKA) in Kampar. Methods of data collection using survey methods. The population in this study were farmer’s who applied this SISKA Program and farmer’s are no longer valid SISKA this program. Samples of this technique is 37 people, including respondents who applied and did not apply this SISKA program. Data analysis used descriptive methods. Variables characteristic role of extension were analyzed using Likert Scale. Results shows that the role of Institutional Extension Support (SISKA) by indicator of education with role category, dissemination information or innovation in quite a role category, facilitation in of less a role category, consultancy in quite a role category, supervision or coaching quite a role category, monitoring and evaluation in quite a role category. The farmer’s perceptions of the SISKA program on the role of education institutions in Kampar obtained with quite a role category. Keywords: Perception, institutions, extension, integration.